Experimental study on energy performance of a mobile biomass-fueled drying furnace using sawdust - Panggabean, Tamaria; Helda, Helda; Robbani, Syifa (Jurnal Polimesin, 2025)
The development of energy-efficient, mobile dryers using biomass fuel remains a challenge, particularly for rural agricultural applications. This study experimentally evaluates the energy performance of a mobile drying furnace fueled by sawdust, focusing on the effects of fuel feeder rotational speed (25, 30, and 35 rpm). Key performance metrics include temperature distribution, fuel consumption rate, thermal efficiency, and energy balance. The furnace is equipped with a screw conveyor, combustion chamber, and heat exchanger, with temperature monitored via IR thermometers. The highest thermal efficiency of 37.64% was achieved at 25 rpm, with a fuel consumption rate of 4.25 kg/h and total energy output of 110,144 kJ. At 35 rpm, energy output peaked at 188,369.12 kJ, but efficiency declined to 22.41% due to incomplete combustion. All settings-maintained outlet air temperatures between 43.08–46.08°C, suitable for grain drying. Energy balance analysis revealed that 80.92% of total input energy was transferred to the drying chamber at 35 rpm. These findings suggest that moderate feeding speeds (25–30 rpm) offer the best trade-off between efficiency and energy delivery, confirming the potential of mobile, sawdust-fueled systems for sustainable drying in off-grid settings.